The influence of profitability, firm size, productivity and reputation of the auditor on the rating of Sukuk. - Galih Estu Pranoto; Ratna Anggraini; Erika Takidah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this research is to find out the effect between the profitability, firm size, productivity, and auditor reputation toward rating sukuk. Rating sukuk is the dependent variables in this research were measured by scoring technique based on Pefindo’s rating. For the independent variables in this research, using profitability were measured by return of equity ratio, firm size were measured by natural logarithm of total asset, productivity were measured by comparison sales with employees, auditor reputation using dummy method. This research using secondary data which is non bank companies from Indonesian Stock Exchange Listed Company and rated by Pefindo in 2009-2013. While the sampling method used was purposive method which is overall 35 sample choose. This research uses logistic ordinal regression to test the hypothesis with SPSS computer program. The research result show that produktivity and auditor reputation partially have a significant negative influence toward rating sukuk, while profitability and firm size have no significant influence toward rating sukuk.